Electrical and Optical Properties of a Transparent Conductive ITO/Ga(2)O(3)/Ag/Ga(2)O(3) Multilayer for Ultraviolet Light-Emitting Diodes - Liang, Siwei (Nanomaterials (Basel), 2019)
We fabricated an indium tin oxide (ITO)/Ga(2)O(3)/Ag/Ga(2)O(3) multilayer as a transparent conductive electrode for ultraviolet light-emitting diodes (UV LEDs). The electrical and optical properties of the multilayer were improved by optimizing the annealing temperature of the ITO contact layer and the whole ITO/Ga(2)O(3)/Ag/Ga(2)O(3) multilayer, and the thickness of the ITO contact layer and Ag metal layer. After optimization, the sheet resistance and transmittance of the ITO/Ga(2)O(3)/Ag/Ga(2)O(3) multilayer was 3.43 Ω/sq and 86.4% at 335 nm, respectively. The ITO/Ga(2)O(3)/Ag/Ga(2)O(3) multilayer also exhibited a good ohmic contact characteristic with a specific contact resistance of 1.45×10(−3) Ω·cm(2). These results show that the proposed ITO/Ga(2)O(3)/Ag/Ga(2)O(3) multilayer is a promising alternative as a p-type electrode for UV LEDs.